Sustainability Accounting and Reporting in the Banking Sector: A Systematic Literature Review: Sustainability Accounting - Paulo Gonzales da Cruz; Aria Farah Mita (Journal of Social Commerce, 2025)
This paper is a systematic literature review (SLR) of research studies on Sustainability Accounting and Reporting (SAR) in the banking industry between 2019 and 2024. Two research questions guide the review: RQ1 investigates the effects of regulatory pressures and stakeholder expectations on the adoption and implementation of SAR; RQ2 will determine the degree to which SAR practices have calculable impacts on environmental performance, social responsibility, and financial risk management. Using the PRISMA protocol, the research team searched the Scopus and Web of Science databases systematically to find applicable literature and obtained an initial pool of 786 records. The next stage of rigorous screening and eligibility evaluation led to the inclusion of 99 articles in the further in-depth analysis. The analytical results suggest that the Stakeholder, Legitimacy, and Institutional theories are productive in underpinning the external forces that trigger banks to embrace SAR. However, the literature inundates a reactive, legitimacy -seeking position among banking institutions. Although SAR is often applied as a strategic tool to bargain legitimacy and control power asymmetries, it is not always a driver of transformative change. The analysis thereby finds a significant discrepancy between the symbolic implementation of SAR, that is more typical within an environment with weak regulatory enforcement and its substantive application, which seems to be conditional upon strong internal capacities and severe regulatory pressure. In terms of the impact dimension, the evidence available of tangible outcomes is mostly associative and heterogeneous and has significant methodological limitations.